Perfektum participium som adjektivisk prædikativ - Schack, Jørgen (Danske Studier, 2024)
This paper discusses -(e)t-forms, i.e. forms such as bevæbn-(e)t and anhold-t, in relation to the verb forms perfect participle and supine. In contemporary Danish, a formal distinction is made between -(e)t-forms with verbal (resultative) and adjectival (propertyascribing) meaning respectively. When used attributively, no such distinction is made, e.g. de anholdte/bevæbnede gerningsmænd. However, when used following the auxiliary verb være, -(e)t-forms with verbal meaning occur in supine constructions, where there is no inflectional agreement in number between the subject and the supine verb form, e.g. gerningsmændene er anholdt. Adjectival -(e)t-forms, on the other hand, occur in predicative constructions, where the -(e)t-forms agree in number with the subject, e.g. gerningsmændene er bevæbnede. It is suggested that -(e)t-forms formed from some verbal stems only occur in verbal contexts, while -(e)t-forms formed from other verbal stems occur in both verbal and adjectival contexts. The ability of an -(e)t-form to participate in adjectival contexts/predicative constructions seems largely to depend on the Aktionsart of the verb that it is formed from.